The Effectiveness of Cognitive Behavior Therapy Group Counseling with Assertive Training and Cognitive Restructuring Techniques to Reduce Social Media Addiction - Jasuma, Nelly Herawati; Sugiyo, Sugiyo; Mulawarman, Mulawarman (Universitas Negeri Semarang, 2023)
Social media addition is the most common problem experienced by students. The cognitive behavior therapy group counseling with assertive training and cognitive restructuring techniques were predicted to reduce this addiction. In line with this assumption, the present study attempted to examine its effectiveness. It used a pretest-posttest control group design and involved 24 students grouped into three. The subjects were selected using a purposive sampling technique with the criteria of students with medium and high social addiction levels. For the data, the current study took them using an instrument of social networking addiction scale which was adopted into Indonesian with the cronbach’s alpha coefficient of 0.92. Based on the Wilcoxon test, both techniques were effective to reduce students’ social media addiction. Further implication and limitation will be available in the discussion chapter.